Effects of doping concentration on bond length and bond energy studied by Raman shift - Yang, Xuexian (2023)
Based on the correlation between Raman shift and bond parameters, and further combined with experimental values of the Raman shift composition effect, the relationship between the composition and bond parameters of the 2D-M1−xM′xX2 and 2D-MX′2xX2(1−x) alloy materials was established. Numerical reproduction of the measurements clarified that the host atom phonons involved interaction with all of its z neighbors, whereas the doping atom phonon only involved interaction with a dimer. The doping of large atoms resulted in an elongation of the bond length, an increase in the equivalent coordination number, and enhancement of the binding energy. The doping of small atoms led to a contraction of the bond length, a decrease in the equivalent coordination number, and a weakening of binding energy. By quantifying the relationship between composition and bond parameters from Raman shifts, a deep understanding of two-dimensional alloy properties can be achieved.